Implementation of Curriculum and Learning Models in Improving the Quality of Education - Amara Mayasena; Amelia Amelia; Aulia Putri; Mohamad Muspawi (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2026)
Curriculum is an essential component in education that needs to be continuously updated to keep pace with the development of the times. This study aims to examine curriculum implementation and the role of learning models in improving the quality of education. The method used is a literature review of relevant sources. The results show that curriculum implementation involves several stages, namely planning, implementation, and evaluation of learning, and is influenced by teacher competence, school management, and facilities and infrastructure. In addition, the use of learning models such as Problem Based Learning (PBL), Project Based Learning (PJBL), Discovery Learning, Inquiry Learning, and Problem Solving can enhance students’ activeness and critical thinking skills. Therefore, effective curriculum implementation and the appropriate selection of learning models can improve the overall quality of education. Keywords: Curriculum Implementation, Learning Models, Quality of Education